(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Aceclofenac, (2-[2-[2-(2, 6-dichlorophenyl) aminophenyl] acety] oxyacetic acid) a non-steroidal anti-inflammatory drug (NSAID), has been indicated for various conditions like post-traumatic pain, rheumatoid arthritis, ankylosing spondylitis. Multiple-unit systems have been reported to avoid the variations in gastric emptying and different transit rates through gastro-intestinal and spread over a large area preventing exposure of the absorbing site to high drug concentration on chronic dosing. The purpose of this study was therefore to develop aceclofenac loaded chitosan microparticles by ionotropic gelation method. Drug loading efficiency (DLE) of microparticles was found between 62.20 to 92.93 % and depended on the formulation variables. Increase in the Tripolyphosphate (TPP) concentration, pH of the TPP solution and cross-linking time decreased the drug release. The particle size decreased with increase in cross-linking time and found between the ranges of 1194.1 to 1568.9 µm. Drug release showed slight burst effect in phosphate buffer pH 7.4 in first hour followed by prolonged release for 8 hrs. FTIR and DSC revealed that there was no interaction between drug and polymer. The release data was fitted into first order, zero order and Higuchi model to find release kinetics. The values of regression coefficient r2 were found to be greater (£ 0.9541) for first order than for zero order (£ 0.8740) and the r2 value for Higuchi was £ 0.9805 suggesting diffusion controlled process. The result concluded that TPP-chitosan microparticles developed by ionotropic gelation method might become potential delivery system to prolonging the release of aceclofenac.